Adipose tissue and its proinflammatory properties - Pluta, Waldemar; Radecka, Aleksandra; Dudzińska, Wioleta; Lubkowska, Anna (Journal of Education, Health and Sport, 2020)
For many years, adipose tissue was considered only as an energy store, additionally having an insulating and protective function against injuries. The discovery of the ob gene more than 20 years ago meant that adipose tissue is now seen as an endocrine gland regulating / modulating the body's energy metabolism, inflammatory and immune processes thanks to the secretion of bioactive molecules such as adipokines, enzymes, hormones and growth factors. The substances secreted by adipose tissue with a pro-inflammatory effect include, among others leptin, resistin, tumor necrosis factor, lipocalin 2, angiopoietin-like protein, interleukin-6, interleukin-18, visfatin, monocyte chemotactic factor 1, chemerin or a plasminogen activator inhibitor.